Myocardial perfusion imaging in a case of cardiac strangulation: A novel approach to detect pacemaker-induced ischemia - Siven Kar; Harshita Gupta; Nusrat Shaikh; Vikram Lele (Annals of Pediatric Cardiology)
Cardiac strangulation is a rare phenomenon in children following epicardial pacemaker implantation, caused by compression of the heart and great vessels by the epicardial pacemaker wires. We report a rare case of cardiac strangulation presenting after 8 years of epicardial pacemaker implantation. On routine follow-up, computed tomography angiography showed significant extrinsic compression of the mid-left anterior descending (LAD) artery by the epicardial pacing wire. She was referred to our department for myocardial perfusion imaging (MPI), which showed significant inducible ischemia in the LAD territory. Following this, she underwent a successful pacemaker reimplantation. MPI can, thus, act as a good tool to assess the functional significance of the compression caused by strangulation of the heart by pacemaker leads in asymptomatic patients.